Amputation-Free Survival and Time-to-Healing in Diabetic Foot Ulcers: A Multistate Competing-Risks Survival Analysis - Asmat Burhan; Maria Angelica Dela Cruz; Grace Tan Wei Ling; Indah Susanti; Napat Kittisak; Eza Kemal Firdaus; Septian Mixrova Sebayang (Indonesian Science Media, 2025)
Background: Diabetes-related foot ulcers (DFUs) remain a major burden in low-resource services, with wide variation in healing and limb outcomes. Evidence using competing-risks or multistate methods to accurately estimate amputation-free survival (AFS) and time-to-healing, and to identify modifiable risks within routine care remains limited. Purposes: This study aimed to estimate AFS and time-to-healing and to test associations of peripheral arterial disease (PAD), kidney function, infection, glycemia, and off-loading with these endpoints among adults with DFUs. Methods: In a multicenter prospective cohort in Indonesia (October 1, 2022-September 30, 2023), we enrolled 620 adults with active DFUs meeting predefined criteria; exclusions included prior major amputation, non-diabetic ulcers, malignancy, incomplete dates, or day-0 loss to follow-up. Outcomes were AFS (first amputation or death) and time-to-healing (complete epithelialization), each under competing risks (amputation/death or healing). We estimated cumulative incidence with Aalen-Johansen and modeled transitions using cause-specific Cox and Fine-Gray sub-distribution hazards, adjusting for prespecified covariates; multiple imputation addressed missingness, proportional hazards diagnostics were performed, and subgroup/sensitivity analyses were prespecified. Results: Among 620 participants (PAD 41.9%, neuropathy 47.1%, infection 35.6%), the 12-month cumulative incidence was: healed 71%, minor amputation 14%, major amputation 4%, and death 8%. PAD, reduced eGFR (<60), infection, and higher HbA1c worsened AFS (sHR 1.78, 1.55, 1.42, and 1.09 per 1% respectively), while higher HbA1c and infection slowed healing (sHR 0.90 and 0.71); PAD reduced healing (0.79), and off-loading improved healing (1.22). Findings were consistent across sensitivity and subgroup analyses, indicating robustness. Conclusion: Most patients healed within 12 months, yet one in four experienced amputation or death. Results support routine vascular triage or revascularization, infection bundles, glycemic or renal optimization, and mandated off-loading within DFU pathways, and motivate further prospective evaluations of durability, safety, and cost-effectiveness.